Seagrass-sediment interactions, positive feedbacks and critical thresholds for occurrence: a review - de Boer, W. F (Hydrobiologia, 2007)
This literature review summarizes the limiting factors for seagrass occurrence, and the effect positive feedbacks in seagrass systems have on these threshold levels. Minimum water depth is mainly determined by wave orbital velocity, tide and wave energy; and maximum depth by light availability. Besides these, other limiting factors occur, such as an upper current velocity threshold, above which seagrasses are eroded, or a lower water current velocity threshold below which carbon exchange is limiting. In some locations organic matter content, sulphide concentration or nutrient availability are limiting. N-limitation is mainly reported from temperate terrigenous sediments, and P-limitation from tropical carbonate sediments. However, limiting factors sometimes change over the year, switching from light limiting to N- or P-limiting, and show at times regional variation. The effect seagrasses have on current reduction, trapping sediment and decreasing resuspension can lead to several changes in both the sediment and the water column. In the sediment, an increase in nutrient availability has been reported, and increases in organic matter, sediment height increases, and burial of the seagrasses. In the water column the effect is a reduction of the turbidity through a decrease of the sediment load, decreasing the attenuation coefficient, thereby increasing light availability. Due to the large effect light availability has on seagrass occurrence, the effect of an improvement of the light conditions by a reduction of the turbidity by seagrasses is probably the most important positive feedback in seagrass systems. The latter effect should therefore be incorporated in models that try to understand or predict seagrass changes. Generalization are difficult due a lack of studies that try to find relationships between seagrass architecture and sediment trapping (studying both turbidity reduction and nutrient increase) on a global level under a variety of different conditions. Areas for research priorities are identified.